DIPG-23. BRAINSTEM RADIATION EXPOSURE CONFERS SUBSTANTIAL RISK OF DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG) IN MEDULLOBLASTOMA SURVIVORS: A REPORT FROM THE INTERNATIONAL DIPG REGISTRY. Issue 2 (22nd June 2018) - Gits, Hunter; Anderson, Maia; Zon, Becky; Howell, Christopher; Kasaian, Katayoon; Qin, Tingting; Stallard, Stefanie; Polan, Daniel; Matuszak, Martha; Leonard, Marcia; Pratt, Drew; Spratt, Daniel; et al.
Abstract: With improved survivorship in medulloblastoma, there has been increasing recognition of the occurrence of secondary malignant brain tumors. To date, no studies have specifically addressed the risk of diffuse intrinsic pontine glioma (DIPG) in medulloblastoma survivors. We queried the International DIPG Registry and identified six cases of DIPG with prior medulloblastoma. Six additional cases were identified in reports from recent cooperative group medulloblastoma trials. Incidence of DIPG after medulloblastoma ranged from 0.3–3.9%. All 12 cases underwent surgical resection followed by craniospinal photon irradiation (range 18–36 Gy) and posterior fossa boost (range 19.8–36 Gy). Posterior fossa exposure was greater than 53 Gy in all cases. Median time to diagnosis of secondary DIPG was 7 years (range 2–11 years). Patients died of secondary DIPG a median of 8 months after diagnosis (range 4–17 months). Molecular subgroup of primary medulloblastomas with available tissue (n=5) revealed only non-WNT, non-SHH subgroups (group 3 or 4). Tumor/germline exome sequencing of three secondary DIPGs demonstrated tumors to be H3.3 wildtype and harbor higher mutational burden than radiation-naïve DIPGs. Mutational signature analysis of secondary DIPGs showed mutations consistent with radiation-induced DNA damage (e.g., insertional event in TP53), as well as mutations in other oncogenic drivers (e.g., NRAS, PI3KCA), suggestive of distinct mutational processes compared with primary DIPGs. In conclusion, we report for the first time that survivors of pediatric medulloblastoma are at risk for the development of secondary DIPG, likely consequent to radiation exposure. This risk highlights the importance of radiation field, volume, and modality in medulloblastoma treatment.